Redescription of Cheirodon ibicuhiensis Eigenmann, 1915 (Characiformes: Cheirodontinae), with Notes on its Distribution in Argentina - Mantinian, Julia Erika (2008)
Cheirodon ibicuhiensis Eigenmann, 1915, is redescribed including new anatomical data based on material collected at sixteen localities in the Lower Paraná and Lower Uruguay River basins in Argentina. This is the first report of the species with accurate localities for this country. C. ibicuhiensis is distinguished from C. interruptus, a morphologically similar and geographically close species, by the following combination of characters: body relatively deep (28.2-39.8% SL) and compressed; snout to anal-fin origin (55-61.7% SL); anal-fin base length (22-31% SL); peduncle depth (8.8-12.6% SL); iv-v, 19-23 anal-fin rays; 17-22 ventral procurrent caudal-fin rays; maxilla with 1-2 teeth; 33-36 scales in the longitudinal series; 6-11 perforated scales on the lateral line. Ecological notes on this species are also provided.